Modification Coefficient Optimization of Series Gear Mechanism based on Multi-objective Genetic Algorithm NSGA-Ⅱ - Li Yaodong; Zhang Min; Miao Pu; Cao Zhongchen; Wang Jiawen (Jixie chuandong)
In order to rationally allocate modification coefficients of a series gear mechanism,a optimization model based on multi-objective genetic algorithm is set up. In the model,the objectives are set as the center distance deviation and variation coefficient of addendum height,and four constraint conditions are taken into account,such as no undercutting,no too thin addendum thickness,no too small contact ratio,no transitional curve interference. A multi-objective genetic algorithm,namely NSGA-Ⅱ method is used to solve the objective function. The modification coefficients of the series gear mechanism are optimized. As the results show,this method is especially efficient to be used to optimize the mechanism modification coefficients. The optimized coefficients accord with engineering practice and fulfill well the design demand.